(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Despite significant advances in medicine, the growth of the cultural level and awareness of the population, there are persistent unfavorable trends in health status. The health status of young people as a significant social group in society is not only an indicator of the country’s socio-economic and social development, but also an important indicator of the labor, economic, cultural, and defense potential of society. Therefore, it is important to know how the health of young people is formed, what factors it depends on, and how these factors can be influenced to achieve positive results.